2015
DOI: 10.2319/091913-690.1
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution in the temporomandibular joint after mandibular protraction: A three-dimensional finite element study

Abstract: Objective: To evaluate the stress patterns in temporomandibular joint (TMJ) during mandibular protraction at different horizontal advancements with constant vertical height in a construction bite using a three-dimensional finite element method. Materials and Methods: A three-dimensional computer-aided model was developed from the magnetic resonance imaging (MRI) of a growing boy (age 12 years) using MIMICS software (version 7.0, Materialise, Leuven, Belgium). Stresses with constant vertical opening of 5 mm cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…4 ). It corresponded to Shrivastava’s [ 39 ] FEA results that compressive stress in the anterior aspect reduced after advancement. Studies have shown that continuous compression on the condylar cartilage decreased the proliferation of chondrocytes and the amount of extracellular matrix [ 45 ], and induced cartilage thinning [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…4 ). It corresponded to Shrivastava’s [ 39 ] FEA results that compressive stress in the anterior aspect reduced after advancement. Studies have shown that continuous compression on the condylar cartilage decreased the proliferation of chondrocytes and the amount of extracellular matrix [ 45 ], and induced cartilage thinning [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown that when condylar chondrocytes experienced pressure unloading as the posterior part of the condyle deviated from the glenoid fossa, they responded biologically to unloading, enhancing their differentiation and maturation, eventually resulting in increased ossification [ 8 , 9 ] and substantial new bone formation in the posterior aspect of condyle [ 42 ]. Existing FEA attributed condylar growth to the increased tensile stress on the condyle in the mandibular advanced position [ 39 , 43 ], while the results of the present study showed that the initial pressure in the superior and posterior aspects of the condyle was released to near zero by AMS (Fig. 4 ).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…1 This aspect is very important from the clinical perspective since it enables to establish the effects of the modification of such parameters during orthognathic surgery and gnathologic or orthodontic treatments. [3][4][5][6] Among mathematical models, the most renowed one is the finite element method (FEM), which originates from the principles of electronic. After many enhancements, FEM is employed nowadays in the biomechanical analysis of the stomatognathic system contributing to the current knowledge despite the difficulties encountered in the evaluation of the mechanical properties of the biological tissues.…”
Section: Introductionmentioning
confidence: 99%